DEVELOPMENT OF NON-TIDAL ADAPTIVE RICE VARIETIES: MOLECULAR MARKER ASSISTED SELECTION OF BC2F1 PROGENIES - Nabilah Amiros; Rujito Agus Suwignyo; Mery Hasmeda; Entis Sutisna Halimi; Fikri Adriansyah (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Submergence stress and drought stress are main abiotic constraints encountered in South Sumatra swampland rice cultivation area. The development of new abiotic stress tolerant varieties through the introgresion of tolerance genes, such as the Sub1 gene (submergence tolerance) by using Marker-assisted Backcrossing (MABC method) is one of an ideal solution to obtain an adaptive rice variety for those conditions. The study was carried out at Faculty of Agriculture, Sriwijaya University, Indonesia. In this study, BC2F1 used as the plant materials derived from backcross performed in BC1F1 and the recipient parent, Inpago 5. Previously, BC1F1 obtained from backcrossed progenies from Inpara 8 (inherited Sub1A gene) and Inpago 5 as recipient parent, a drought tolerant variety. The main objective of this study was to analyze the Sub1 introgressed plants in backcrossed progeny BC2F1 that closest similarity to recipient parent. The result showed that Sub1 introgression was confirmed by a tightly linked Sub1 gene marker, SUB1C173 marker. Out of 47 plants, 20 plants were selected based on foreground selection. Those plants were further analyzed on background selection by using 13 SSR markers. Based on the foreground and background selection, two plants, viz, plant no. 41 and 44, were selected and will be used for further study.